Molecular mechanisms of Tau protein aggregation inhibition - Akoury, Elias (2013)
Of all neurodegenerative diseases, Alzheimer´s Disease is the most widespread dementia syndrome, exhibiting progressive memory loss and intellectual abilities. One of the pathological hallmarks of this disease is associated to the presence of abundant intracellular deposits of the Tau protein. Accumulation of these stable species is a multistep process that involves the formation of various transients. Understanding this key step may eventually enable to obstruct aggregation. Tau protein is an intrinsically disordered protein, abundant in neuronal axons where it promotes and stabilizes microtubule assembly. Chapter 1 discusses the physiological function and pathological consequences of this protein and sheds light on the current Taubased research implemented in therapeutic strategies. This chapter also reviews the identification of inhibitors of Tau aggregation as potential disease-modifying drugs; with a detailed discussion of two organic compounds we have recently screened, Phthalocyanine Tetrasulfonate and Phenothiazine Methylene Blue. The same chapter then introduces the Heat shock proteins and their role in Tau clearance. The chapters that follow report our research investigation of aggregation inhibitors and chaperonic partners of Tau where we used an integrated approach to detect possible assemblies of pathogenic conformational transitions. Chapter 2 represents the Phthalocyanine tetrasulfonate study and its inhibition of Tau filament formation by conformational modulation. Chapter 3 investigates the mechanistic basis of the phenothiazine-driven inhibition of Tau aggregation. Chapter 4, examines how the imbalance of Hsp70 family variants fosters Tau accumulation. As a final point, the significance of the biophysical techniques incorporated in the three published manuscripts are briefly discussed in the last part of Chapter 1.